Enhancing EAP students’ academic writing and AI literacies: practice at a transnational university in China - He, Huimin; Tinsley, Joseph (Journal of China Computer-Assisted Language Learning, 2025)
As Generative AI is increasingly used by language learners for academic writing in the context of higher education, it becomes essential for educators to integrate AI literacies in the writing curriculum to guide students to use Generative AI effectively, critically and ethically. We aim to share our practice in relation to AI literacy training for English academic writing among EAP learners studying at a joint-venture EMI university in China. Specifically, learning activities were designed and implemented for students to understand Gen AI’s advantages and pitfalls, engineer effective prompts, enhance assessment literacies, exercise critical thinking and safeguard academic integrity during the process of using GenAI for academic writing. In addition, the pedagogical considerations and rationale behind the practice will be illustrated. Finally, the article will be concluded with reflection on the practice and further suggestions on delivering AI literacy training for language learning purposes.